2010
DOI: 10.1007/s10493-010-9400-x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption rate and functional response of the predaceous mite Kampimodromus aberrans to two-spotted spider mite Tetranychus urticae in the laboratory

Abstract: Prey stage preference of female Kampimodromus aberrans (Oudemans) (Phytoseiidae) at constant densities of different stages of Tetranychus urticae Koch (Tetranychidae), functional response types and parameters of the predator females to the varying densities of eggs, larvae, protonymphs and deutonymps of T. urticae were determined in order to establish its potential for the mite biological control. Experiments were conducted at 25 ± 1 °C, 65 ± 10% RH and 16:8 (L:D) photoperiod. Our results indicated that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
2
10
1
Order By: Relevance
“…In A. andersoni the highest values were associated with the lowest prey density and the optimal ratio was obtained when four prey were offered per day. The results obtained in the response of the three predatory mites species to E. carpini density show some similarities to those found for these predatory mites (laboratory colonies) fed with prey other than E. carpini (e.g., Dicke et al 1988;Koveos and Broufas 2000;Lester and Harmsen 2002;Kasap and Atlihan 2011). To our knowledge the present study is the first where the response of the three predatory mites species to prey density has been investigated in the same conditions and using the same prey.…”
Section: Discussionsupporting
confidence: 77%
“…In A. andersoni the highest values were associated with the lowest prey density and the optimal ratio was obtained when four prey were offered per day. The results obtained in the response of the three predatory mites species to E. carpini density show some similarities to those found for these predatory mites (laboratory colonies) fed with prey other than E. carpini (e.g., Dicke et al 1988;Koveos and Broufas 2000;Lester and Harmsen 2002;Kasap and Atlihan 2011). To our knowledge the present study is the first where the response of the three predatory mites species to prey density has been investigated in the same conditions and using the same prey.…”
Section: Discussionsupporting
confidence: 77%
“…Consumption rate of the predators is generally inversely related to prey size (Kasap & Atlihan 2011) but in this study, consumption rate of N. californicus of Tetranychus larvae was the highest, followed by the nymphs, and the consumption rate of eggs is the lowest. This might be due to the fact that larvae and nymphs of Tetranychus fed in clusters which make them relatively easy to handle them.…”
Section: Discussioncontrasting
confidence: 59%
“…However, Ibrahim and Palacio (1994) noted that N. longispinosus preferred larvae and nymphs of Tetranychus urticae to eggs. The predatory mites N. californicus (Canlas et al 2006) and Kampimodromus aberrans (Kasap and Atlihan 2010) also showed preference for larvae when fed T. urticae .…”
Section: Discussionmentioning
confidence: 99%